China and the West - Franke, Wolfgang; Wilson, R. A. (Oxford : Basil Blackwell, 1967)
This collection scrutinises how China and the West interact in aspects of culture, arts, politics and everyday life.
Includes bibliographical references and index.
Keywords: Arts -- China; China -- Foreign public opinion; China -- Foreign relations